A shear deformation theory for bending and buckling of undersea sandwich pipes. (15th November 2015) - Xue, Jianghong; Wang, Yiou; Yuan, Ding
Abstract: In this paper, a first order shear deformation theory is proposed for cylindrical sandwich pipes subjected to undersea water pressure. The new model examines the change of the circumferential radius due to the radial deflection of the cylindrical sandwich shell and its effect on the bending moments. Differential equations of equilibrium for the non-shallow cylindrical sandwich shell are derived and are expressed in terms of the components of displacement and the rotation angles of the middle planes of the face sheets with respect to the neutral surface. The proposed theory is applied to investigate the buckling of a thermal insulating sandwich pipe laid on the seabed with fully constraint ends. Numerical analyses are conducted by developing MATLAB program to obtain the buckling pressures as well as the corresponding half wave numbers in circumferential direction for cylindrical sandwich pipes for different slenderness ratio, radius-to-thickness ratio and core-to-facesheet thickness ratio. The efficiency and accuracy of the presented theory is confirmed by comparing the analytical solutions with finite element results from ABAQUS, both showing a good agreement with each other.